Holocene geochemical data from alpine wetlands in southern Spain - Antonio García-Alix; Francisco Jose Jiménez-Espejo; Gonzalo Jiménez-Moreno; Jaime L Toney; María J Ramos-Román; Jon Camuera; R Scott Anderson; Antonio Delgado Huertas; Francisca Martínez Ruiz; Ignasi Queralt (PANGAEA, 2017)
This dataset includes all the geochemical data available, both organic and inorganic ones, from Holocene sedimentary records of alpine wetlands in Sierra Nevada (southern Spain). These sedimentary records come from four sites at different elevations, ranging from 2497 to 3020 masl: Laguna de la Mula (shallow lake, 2497masl), Borreguil de la Virgen (bog, 2945masl), Laguna de Río Seco (lake, 3020masl), and Borreguil de la Caldera (bog, 2992masl). The studied sediments registered both the external mechanisms that generated the sedimentary records in these alpine wetlands during the Holocene (from both natural and anthropogenic sources), such as runoff, aeolian input, or pollution, as well as the ecosystem response to these natural and anthropogenic forcing.